THE ROLE OF THE GEOMETRY COURSE IN THE ACADEMIC LYCEUM IN THE DEVELOPMENT OF INTELLECTUAL SKILLS - Kundizkhan Kuralbayqizi Tolibayeva (Web of Journals Publishing, 2023)
Improvement of problem-solving skills is of great importance in expanding and developing creative thinking skills in youth. This article is devoted to the problems and opportunities of developing individual creative thinking in students by solving geometric problems in various unique ways.
Keywords: creative activity, skill, communicative, literacy, concept.